Photoconductive Metal-Organic Frameworks Based on 10,20-Meso-Substituted Zn-Porphyrin and Fullerene c60 - Cardenas-Jiron, G; Granados-Tavera, K; Montenegro-Pohlhammer, N (Elsevier B.V., 2023)
Metal-organic frameworks (MOFs) with electrical conductivity have potential applications as electrochemical sensors, electrocatalysis, and energy storage. We present the design of a new class of conductive MOFs based on porphyrin, substituted in the 10,20 meso-positions (1 amine, 2 hydroxy, 3 methoxy, 4 nitro, and 5 dimethylamine). Furthermore, these MOFs are doped with fullerene molecules (C60) within their pores, resulting in 1@C60, 2@C60, 3@C60, 4@C60, and 5@C60. To study the electronic and optical properties of these MOFs before and after the incorporation of C60, theoretical calculations based on density functional theory (DFT) (PBE+D3/DZP) and time-dependent DFT (TPSSh/6-31G) were performed. Incorporating C60 causes a decrease in the bandgap of MOFs due to its unoccupied crystalline p orbitals (LUCOs). It also promotes the Q and Soret (B) bands of porphyrin in the MOF to absorb at longer wavelengths. Charge transport properties were calculated using the Keldysh nonequilibrium Green s function (NEGF) formalism and molecular junctions with Au(111)-based electrodes for 1 and 1@C60. When a bias voltage of 0.2 V is applied, an increase in current is obtained for 1@C60 concerning 1. Our results suggest that MOF@C60 is a promising alternative for designing new photoconductive materials because of the donor-acceptor interactions generated. © 2023 Elsevier B.V.